009: FIELD MONITORING OF THE Z BENEFITS FOR BREAST CANCER OF THE PHILIPPINE HEALTH INSURANCE CORPORATION. (24th August 2015) - Reyes, Merla Rose D; Santillan, Melanie C; Tacang, Aristides L; Vecina, Gemma S; Calabio, Daryl Ruviro C; Tacang, Aristides L; Lanuza, Arhur M; Soria, Francisco Z; Lavina, Shiela Marie S
Abstract : Background: Philippine Health Insurance Corporation developed the Z benefits health care package for conditions that are medically and economically catastrophic in order to provide financial protection and reduce out-of-pocket expenses. The Z benefit package for breast cancer provides insurance coverage for stages 0 to IIIA and was implemented in 2012. Objectives: To determine the direct out-of-pocket expenses (co-payments) and overall satisfaction among patients enrolled in the Z Benefits for breast cancer. Methods: The database of paid claims was the sampling frame of the study. Participants were identified and trained data collectors conducted patient interviews using a pre-tested semi-structured survey tool. Participants signed an informed consent for an interview, audio and video documentation of feedbacks. Clinical data were extracted from medical records while out-of-pocket expenses were reviewed from statements of account and receipts of services received. Patient satisfaction during surgery, chemotherapy and overall patient satisfaction were validated with the satisfaction questionnaires submitted by the contracted hospitals. Result: A total of 80 claims for breast cancer using the Z benefit package were identified from July 2012 to August 2014 from five contracted hospitals. Respondents underwent modified radical mastectomy with 50 patients receiving standard adjuvant chemotherapy. During hospital confinement, 41 patients purchased medicines outside the hospital pharmacy. The overall average out-of-pocket expense was at Php 3600 (US$80). The average out-of-pocket expense was Php 4000 (US $89) for medicines, Php 1600 (US$36) for laboratory tests and Php 4200 (US$93) for professional fees which are within the allowed co-payment limits. Patient satisfaction was generally good with satisfaction rates of 98% and 92% for surgery and chemotherapy services, respectively. Conclusion: The overall patient satisfaction is favourable but there were still out-of-pocket expenses for medicines, laboratory tests and professional fees amounting to an average of Php 3, 600 (US$80).